2007
DOI: 10.1111/j.1365-2230.2007.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of port-wine stains with the 595-nm pulsed dye laser: a pilot study in Chinese patients

Abstract: The 595-nm pulsed dye laser (PDL) is one of the newest developments in the treatment for port-wine stains (PWS). The aim of this study was to investigate the effectiveness of the treatment of PWS in Chinese patients using the 595-nm PDL. In total, 184 patients with PWS over the face, neck and trunk or limbs were enrolled in the study. All the patients were treated with the 595-nm PDL 3-6 times, with a 4-week interval between each treatment. Treatment parameters varied for each patient according to the colour a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
0
8
1
3
Order By: Relevance
“…A large pilot study conducted on Chinese patients with skin Types III and IV reported >75% improvement in 62.5% of cases and 50% to 75% lightening in 20.7% of patients, with a PGA score of 8 after a mean of 8 sessions (range: 3-12) with the 595-nm PDL. 11 These results were superior to those observed in both Korean and the authors' patients because the PWS were predominantly pink or red and these patients were of lighter skin type than the authors' cases. The moderate response rate observed in the authors' patients was probably because of the older age of patients at the time of intervention, large size of PWS, inclusion of many patients with dusky red to purple lesions, and restricting the number of laser sessions to 10, besides a higher skin phototype.…”
Section: Discussioncontrasting
confidence: 41%
“…A large pilot study conducted on Chinese patients with skin Types III and IV reported >75% improvement in 62.5% of cases and 50% to 75% lightening in 20.7% of patients, with a PGA score of 8 after a mean of 8 sessions (range: 3-12) with the 595-nm PDL. 11 These results were superior to those observed in both Korean and the authors' patients because the PWS were predominantly pink or red and these patients were of lighter skin type than the authors' cases. The moderate response rate observed in the authors' patients was probably because of the older age of patients at the time of intervention, large size of PWS, inclusion of many patients with dusky red to purple lesions, and restricting the number of laser sessions to 10, besides a higher skin phototype.…”
Section: Discussioncontrasting
confidence: 41%
“…Or, les publications sur l'utilisation du LCP sur les angiomes des membres sont moins nombreuses et l'efficacité du LCP est moindre dans cette localisation. Ainsi, les études montrent en moyenne que le LCP permet d'obtenir 70 à 90 % de « bons » à « excellents » résultats sur les angiomes plans de la face contre seulement 20 à 40 % sur les membres [28][29][30][31]. Ainsi, une étude rétrospective [28] de 39 patients ayant eu un traitement par LCP d'angiomes plans de membre inférieur a montré des résultats jugés « bons » à « excellents » dans 38 % des cas et « moyens » dans 40 % des cas.…”
Section: Traitement à Visée Esthétique De L'angiome Planunclassified
“…During the past two decades, the use of lasers for the treatment of PWS has been extensively studied, and it has been found that PDL constitutes a highly effective and safe method as compared to other methods, due to the fact that the laser beam is only absorbed by the vessels, resulting in their selective damage and leaving the surrounding tissues intact. PDL was firstly developed for the treatment of PWS and for many years it has been the treatment of choice [8,10,33] , since it results in a better outcome as compared to Intense Pulsed Light (IPL) [34] . However, the more mature (hypertrophic and nodular) PWS usually respond less adequately to treatment [2,8] .…”
Section: Port-wine Stainsmentioning
confidence: 99%